Konsep Arsitektur Tradisional Sunda Masa Lalu dan Masa Kini - Gatot Suharjanto (Bina Nusantara University, 2014)
It is known that traditional architectures are a product of human conception full of culture and philosophy, while modern architectural concepts prioritize functionality and simplicity that tends to be simple or quick. Now the architectural concept slowly changes according to the conditions of time, then so is the existence of works of architecture that also changes. This condition can be found in almost major cities in Indonesia, where many houses or buildings built still in traditional architecture theme but combined and matched with modern architecture concept. One of many diverse cultures of Indonesia archipelago architecture that has evolved is West Java. There are a lot of people trying to apply the concept of Sundanese traditional house in their residence. Shifting sacred values in traditional concept seems indeed to be lost along with the differences in modern human civilization.